Effect of unsteady cavitation on hydrodynamic performance of NACA 4412 Hydrofoil with novel triangular slot - Sayan Biswas; R. Harish (Heliyon)
This study demonstrates the hydrodynamic performance of a modified NACA 4412 hydrofoil and compares it with the base NACA 4412 hydrofoil in the presence of cavitation. A triangular slot has been introduced at the mid-section of the suction side of the hydrofoil to modify the flow characteristics and assess its effects on the performance at different operational cavitation numbers spanning from 0.8 to 2.5, and at different angles of attack ranging from 4° to 16°. The performance metrics considered include the coefficient of lift, coefficient of drag, and the lift-to-drag ratio. The Reynolds number considered in this study is approximately 1.5 million. The SST k-ω turbulence model, homogeneous mixture multiphase model, and Schnerr& Sauer cavitation model have been employed in this study. At lower cavitation numbers, the modified hydrofoil is better able to control cavitation phenomena compared to the base hydrofoil. However, at higher cavitation numbers, the base hydrofoil exhibits slightly better performance than the modified hydrofoil in terms of lift-to-drag ratio, despite having a lower lift coefficient. Furthermore, the modified hydrofoil demonstrates improved performance at 4°, 8°, and 16° angles of attack, while the base hydrofoil performs better at a 12° angle of attack. It was also observed that stalling occurs at a 16° angle of attack for the base hydrofoil, whereas the modified hydrofoil successfully avoids stalling.